An Intelligent Chess Piece Detection Tool - Menezes, Richardson; Maia, Helton (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2023)
Chess is one of the most researched domains in the annals of artificial intelligence. The main objective of this research is to develop a platform that can determine piece positioning during chess games. Digital image processing methods and real-time object detection (YOLO version 4) algorithms were used during computational development. The problem entails analyzing images captured during a chess game and determining the location of each square on the board, as well as the position of each piece in play. This procedure is repeated at each game turn, enabling the developed system to save and watch all piece moves during a game. The obtained results demonstrate the system’s reliability and feasibility.